Classification of auditory selective attention using spatial coherence and modular attention index. (November 2018) - de Souza, Ana Paula; Soares, Quenaz B.; Felix, Leonardo B.; Mendes, Eduardo M.A.M.
Highlights: Spatial coherence using contralateral attention index is a tool for auditory BCI. A new method is proposed using modular attention index. The method is used for classifying auditory selective attention. Best results were obtained mainly in central, frontal, occipital and parietal areas. Abstract: Background and Objective: Brain-Computer Interfaces (BCIs) based on auditory selective attention have been receiving much attention because i ) they are useful for completely paralyzed users since they do not require muscular effort or gaze and ii ) focusing attention is a natural human ability. Several techniques - such as recently developed Spatial Coherence (SC) - have been proposed in order to optimize the BCI procedure. Thus, this work aims at investigating and comparing two strategies based on spatial coherence detection: contralateral and modular classifiers. The latter is a new method using modular attention index. The new classifier was developed to implement an auditory BCI where a volunteer makes binary choices using selective attention under the amplitude-modulated tones stimulation. Methods: Contralateral and modular classifiers were applied to the electroencephalogram (EEG) recorded from 144 subjects under the BCI protocol. The best set of parameters (carriers of the stimulus, channels and trials of signal) for this BCI was investigated taking into consideration the hit rate and the information transfer rate. Results: The best result obtained using the modular classifier was a hit rate of 91.67% and information transfer rate of 6.74 bits/min using 0.5 kHz/4.0 kHz as stimuli and three windows (5.10 sec of EEG signal). These results were obtained with five electrodes (C3, P3, F8, P4, O2) using exhaustive search to identify regions with greater coherence. Conclusion: The modular classifier - using electroencephalogram channels from the central, frontal, occipital and parietal areas - improves the performance of auditory BCIs based on selective attention.